Pengelolaan Zakat Produktif di BAZNAS Ditinjau dari Hukum Islam - Nur Sholikin (ZAWA: Management of Zakat and Waqf Journal, 2022)
Zakat is one of the pillars of Islam that must be fulfilled by every Muslim who already has assets according to the nishab. Distribution of zakat by muzakki can be given directly to mustahik or through amil. The distribution of zakat in Baznas can be categorized into two forms, namely the distribution of zakat consumptively and productively. The purpose of this research is to find out how the management of productive zakat in Baznas will be reviewed from Islamic law/ownership theory. This research is a field research and to achieve this goal the author uses a descriptive qualitative approach. In this study, primary data was obtained from interviews with Baznas managers and the assistant team from Baznas. Secondary data is obtained from books, journals and related laws and regulations. The results of the study indicate that the management of zakat in Baznas is in accordance with Islamic law/ownership theory in which the management of zakat funds in Baznas has been distributed to those who are entitled to receive it, namely mustahik who are included in the 8 (eight) ashnaf category.